Respon Pertumbuhan Dan Produksi Beberapa Varietas Jamur Tiram Pada Kombinasi Media Serbuk Limbah Pelepah Kelapa Sawit Dan Serbuk Gergaji - Meidaya Bate’e; Ellen Lumisar Panggabean; Siti Mardiana (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
The demand of oyster mushroom has increased. Hence the production should be improved as well. The purpose of research is to know the growth response and production of several varieties of oyster mushroom on the powder media of palm stem waste and sawdust. Research conducted in Sumatra mushroom oyster cultivation. The design used in this study is a Complete Random Design (CRD) factorial that is of 2 factors. The first factor is the composition of the planting media of palm oil and sawdust was conducted with 2 repeats. The Parameter of observation on the study is the percentage of baglogs covered by mycelium (%), the growth of mycelium on the substrate (cm), the age of the body of the fruit (DAI), Number of fruit body (fruit), diameter of the hood (cm2) The stem length of the fruit body (cm) and the wet Harvest weight (g). The results showed that the best treatment for the growth of mycelium and the age of fruit body in total saw dust amd and varieties jamur tiram 58.38 days formation of the first fruit body.